Assessing Knowledge Gaps and Management Needs to Cope With Barriers for Environmental, Economic, and Social Sustainability of Marine Recreational Fisheries: The Case of Spain - Pita, Pablo; Alós, Josep; Antelo, Manel; Artetxe, Iñaki; Biton-Porsmoguer, Sebastián; Carreño, Arnau; Cuadros, Amalia; Font, Toni; Beiro, José; García-Charton, Jose A.; Gordoa, Ana; Hyder, Kieran; et al. (Frontiers in Marine Science, 2020)
The European Parliament is concerned about the lack of information on the relevance of nine million Europeans engaged in marine recreational fishing (MRF), committing Member States to encourage environmental and socioeconomic sustainability of the sector. The objective of this paper is to provide recommendations to guide research actions and management policies, based on the case of Spain, a key country because its complex administrative regimen and the intensive use of its coasts, including 900 000 recreational fishers. A review of the state of the knowledge was performed to identify research gaps, while governance challenges were identified in an International Symposium on Marine Recreational Fishing. In the last two decades research on MRF was remarkable (139 publications). However, public investment in research (€2.44 million in the same period) should be improved to cover knowledge gaps on socioeconomic relevance, on impacts on vulnerable species and on implications of global warming. The license system should be standardized to allow estimation of effort, catch and expenditure. Social networks, mobile applications, fisher ecological knowledge and citizen science programs could help to develop cost-effective research and management. Science-based, adaptive policies should improve the allocation of resources between MRF and other stakeholders, introducing co-management to reduce conflicts.